Burnout among expatriate and local instructors in Oman - Mukundan, Jayakaran; Geng, Hui; Nimehchisalem, Vahid; Al-Busaidi, Saleh (SAGE Publications, 2024)
Burnout, recognized as a psychological syndrome, stems from enduring reactions to emotional and interpersonal obstacles at work. It highlights the tension experienced by individuals within the broader framework of their interactions with their jobs. This phenomenon has attracted considerable attention across diverse professional sectors. With the Middle East’s rapid expansion of tertiary education and reliance on both local and expatriate educators, a thorough understanding of burnout becomes essential. This study aims to investigate the burnout levels experienced by university instructors in Oman and to explore the relationship between their profiles and the three burnout components: Emotional Exhaustion (EE), Depersonalization (DP), and Personal Achievement (PA). Using the adapted Maslach Burnout Inventory (MBI) questionnaire consisting of 22 items, a survey was conducted on a sample of 149 instructors with individual characteristics from public universities in Oman. Regarding burnout, the results showed a moderate level of DP (6.7) and PA (34.8), and a low level of EE (21.5) based on the overall scores. Through bootstrap multiple regression analysis, the results showed that instructors who have lower educational qualifications, lack training support, or are native to the region typically experience higher EE than their counterparts. Male instructors with lower educational qualifications, lower incomes, and local citizenship generally exhibit higher levels of DP compared to their counterparts. Female instructors tend to display higher levels of PA than their male counterparts. These findings highlight burnout in Omani university instructors, guiding future studies to pinpoint causes and tailor interventions in an evolving educational landscape.